Policy systems and measures for the social economy in Seoul - Kil-Soon Yoon; Sang-Youn Lee (United Nations Research Institute for Social Development (UNRISD), 2020)
Seoul has played a leading role in the development of the social economy. It is the capital city of the Republic of Korea as well as the centre of its economic, social, and cultural activities; Seoul possesses abundant resources, relatively mature civil society capabilities, and a city government with the political will to support its social economy. In terms of the establishment of legal and institutional frameworks as well as the development of public polices, Seoul has become a good example not only for other local governments but also for its own central government for its approach to the social economy as a whole as well as to each type of social economy enterprise. The authors introduce the legal and institutional frameworks and public policies that led the growth and development of the social economy in Seoul. Their achievements and limitations are examined, with a focus on the essential components of policy ecosystems for the social economy enabling SEEs to thrive over time, that is, the legal and institutional frameworks for the social economy, social finance and preferential public procurement for social economy enterprises (SEEs), and education and training to foster social entrepreneurship and raise public awareness of the social economy. In doing so, the paper considers the essential components in relation to legal and institutional frameworks and public policies from the central government, because the former has played a role in guiding the latter, but they have also developed together.
Keywords: 330; Sozialökonomik; Institutionenökonomik; Wirtschaftswachstum; Kommunalverwaltung; Seoul